Mediation in the World of Commercial Dispute Litigation: An Inside Look at the Challenges for Counsel, Mediators, and Insurance Claims Professionals - Jeff Trueman (Washington University Journal of Law & Policy, 2020)
This Article examines the professional roles of all parties during commercial mediation. Through a qualitative research project, this author examined the challenges, frustrations, and concerns faced by participants during the mediation of litigated commercial disputes. As a result of these qualitative surveys, similar challenges and frustrations emerge in the mediation process. Specifically, a study in contrasts emerges, similar to the paradox between competition and cooperation. These contrasts exist with all parties to the mediation process.
Keywords: commercial mediation; commercial dispute litigation; professional roles; mediator; mediators; counsel; insurance claims professionals; insurance claims